PENGARUH PERENDAMAN TELUR MENGGUNAKAN LARUTAN DAUN KELOR TERHADAP KUALITAS INTERNAL TELUR AYAM RAS - Riawan, Riawan; Riyanti, Riyanti; Nova, Khaira (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2017)
The purpose of this research was to find out interior quality of egg laying hens which immersion with moringa leaf solution and to find out the best moringa leaf solution. This research carried out on August 14–September 13, 2016 housed in the Laboratory Animal Production and Reproduction, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The material of research used 72 eggs laying hens strain isa brown from layer of 60 weeks old with the average weight 63,0±1,51 gram and coefficient of variation 2,40%. This research used a Completely Randomized Design with 4 treatments and 6 repetition. The treatments of research consists of immersion egg used moringa leaf solution 0% (w/v), 10% (w/v), 20% (w/v), and 30% (w/v). Analyzed data observation used variance with 5% trust level and continued with Least Significant Different test. The result showed that immersion egg with moringa leaf solution significant effect (P<0,05) increase albumin index and the haugh unit, and not significant effect (P>0,05) to yolk index and percentage egg weight lo. Concentration 30% of immersion moringa leaf solution to give the best treatment to interior quality of egg laying hens. Keywords : Albumin Index Moringa Leaf, Percentage Egg Weight Lost, Yolk Index, Haugh Unit.